Acipenser baerii Brandt 1869 ... - Çiçek, Erdoğan; Jawad, Laith; Eagderi, Soheil; Esmaeili, Hamid Reza; Mouludi-Saleh, Atta; Sungur, Sevil; Fricke, Ronald (Zenodo, 2023)
Acipenser baerii Brandt, 1869 Remarks. This species was reported by Mousavi-Sabet et al.(2019) from Tigris River. 34°33′0.39′′N, 045°46′20.02′′E) and from the Ghuretu Stream where it enters the reservoir (34°32′42.11′′N, 45°47′33.59′′E) (both about 1.5-3.5 km away from the cage-culture farm within the reservoir) in the Tigris-Euphrates basin, Kermanshah Province, western Iran, at the border of Iraq. Its presence and establishment success in Iraq should be confirmed by specimen. ... : Published as part of Çiçek, Erdoğan, Jawad, Laith, Eagderi, Soheil, Esmaeili, Hamid Reza, Mouludi-Saleh, Atta, Sungur, Sevil & Fricke, Ronald, 2023, Freshwater fishes of Iraq: a revised and updated annotated checklist- 2023, pp. 1-49 in Zootaxa 5357 (1) on page 39, DOI: 10.11646/zootaxa.5357.1.1, http://zenodo.org/record/10012543 ...